Significance of Critical Thinking through Education in Countering Violent Extremism in Pakistan - Muhammad Ansar Naseer; Ghazala Shaheen (Information Technology and Science (ITScience), 2023)
Pakistan is not an exception to the severe problem that violent extremism poses to nations worldwide. This article examines how important education is in preventing violent extremism and promoting a more accepting and inclusive society. Education gives people the skills they need to reject extremist beliefs and look for peaceful ways to resolve disputes by encouraging critical thinking, religious and cultural tolerance, and civic ideals. The article evaluates current programs in Pakistan, including the